RANCANGAN E-REPOSITORI UNTUK MENDUKUNG KNOWLEDGE MANAGEMENT SYSTEM (KMS) PADA SMA PGRI 24 JAKARTA - Ahmad Fitriansyah; Suryadi Suryadi (JRIS : Jurnal Rekayasa Informasi Swadharma, 2021)
This study aims to produce a prototype of a knowledge management system at SMA PGRI 24 Jakarta. Currently, knowledge management, especially regarding standard operating procedures (SOPs) or work references at SMA PGRI 24 Jakarta, has not been carried out, so that the process of reviewing knowledge in the past cannot be carried out due to several factors, including constraints in the process of finding documents or archives. , because the document archiving method still uses conventional or manual methods, there is no computerized archive storage area, and there is no special knowledge sharing or knowledge sharing media so that the knowledge sharing process becomes less than optimal. The research method used is a field study by conducting observations and interviews as well as the waterfall method in the design of the system. The results of the study are the prototype of a knowledge management system (KMS) that can store both tacit knowledges and explicit, which can be a solution for managing standard operating procedure (SOP) documents, helping in the activities of digitizing archiving, searching for documents and as a means of sharing knowledge.